Patients with Atrial Fibrillation in Clinical Practice: Comorbidity, Drug Treatment and Outcomes (Data from RECVASA Registries) - M. M. Loukianov; E. Yu. Andreenko; S. Yu. Martsevich; S. S. Yakushin; A. N. Vorobyev; K. G. Pereverzeva; A. V. Zagrebelnyy; E. Yu. Okshina; V. V. Yakusevich; V. Vl. Yakusevich; E. M. Pozdnyakova; T. A. Gomova; et al. (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To study comorbidity, drug therapy and outcomes in patients with atrial fibrillation (AF) included in the outpatient and hospital RECVASA registries.Material and methods. Patients with AF (n=3169; age 70.9±10.7 years; 43.1% of men) in whom comorbidity, drug therapy, short-term and longterm outcomes (follow-up period from 2 to 6 years) were included in hospital registers RECVASA AF (Moscow, Kursk, Tula), as well as outpatient registers RECVASA (Ryazan) and RECVASA AF-Yaroslavl.Results. Outpatient registries (n=934), as compared to hospital registries (n=2235), had a higher average age of patients (73.4±10.9 vs 69.9±10.5; p<0.05), the proportion of women ( 66.2% vs 53.0%; p<0.0001) and patients with combination of 3-4 cardiovascular diseases (CVD), including AF (98.0% vs 81.7%, p<0.0001), and also with chronic noncardiac diseases (81.5% vs 63.5%, p<0.0001), the risk of thromboembolic complications (CHA2DS2-VASc 4.65±1.58 vs 4.15±1.71; p<0.05) and hemorrhagic complications (HAS-BLED 1.69±0.75 vs 1.41±0.77; p<0.05), as well as a lower frequency of prescribing appropriate pharmacotherapy for CVD (55.6% vs 74.6%, p<0.0001). During the observation period, 633 (20.0%) patients died, and in 61.8% of cases - from cardiovascular causes. The mortality rate in one year in Moscow was 3.7%, in Yaroslavl - 9.7%, in Ryazan - 10.7%, in Kursk - 12.5% (on average for four registers - 10.3%). A higher risk of death (1.5-2.7 times) was significantly associated with age, male sex, persistent AF, history of myocardial infarction (MI) and acute cerebrovascular accident (ACVE), diabetes mellitus, chronic obstructive disease lungs (COPD), heart rate>80 bpm, systolic blood pressure <110 mm Hg, decreased hemoglobin level. A lower risk of death (1.2-2.4 times) was associated with the prescription of anticoagulants, angiotensin-converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARBs), betablockers, statins. The number of cases of stroke and MI was, respectively, 5.1 and 9.4 times less than the number of deaths from all causes. The higher risk of stroke in patients with AF during follow-up was significantly associated with female sex (risk ratio [RR]=1.61), permanent AF (RR=1.85), history of MI (RR=1.68) and ACVA (RR=2.69), HR>80 bpm (RR=1.50). Anticoagulant prescription in women was associated with a lower risk of ACVA (if adjusted for age: RR=0.54; p=0.04), in contrast to men (RR=1.11; p=0.79).Conclusion. The majority of patients with AF registries in 5 regions of Russia had a combination of three or more cardiovascular diseases (73.9%), as well as chronic non-cardiac diseases (68.8%). The frequency of proper cardiovascular pharmacotherapy was insufficient (68.6%), especially at the outpatient stage (55.6%). Over the observation period (2-6 years), the average mortality per year was 10.3%, but at the same time it differed significantly in the regions (from 3.7% in Moscow to 9.7-12.5% in Yaroslavl, Ryazan and Kursk). Cardiovascular causes of deaths occurred in 62%. A higher risk of death (1.5-2.7 times) was associated with a history of stroke and MI, diabetes mellitus, COPD, heart rate>80 bpm, systolic blood pressure <110 mm Hg, decreased hemoglobin level. However, the risk of death decreased by 1.2-2.4 times in cases of prescription of anticoagulants, ACE inhibitors / ARBs, beta-blockers and statins. The risk of ACVA and MI was the highest in the presence of the history of this event (2.7 and 2.6 times, respectively). Anticoagulant prescription was significantly associated with a reduced risk of stroke in women.